Identification of rheological parameters of the linear viscoelastic model of two species of tropical wood (Tectona grandis Lf and Diospyros mespiliformis) - HOUANOU, KOCOUVI AGAPI; TCHEHOUALI, DÈFODJI ADOLPHE; FOUDJET, Erick Amos (My University, 2012)
The present work aims to determine the rheological parameters for Tectona grandis L.f and Diospyros mespiliformis considering a Zener model. To achieve that goal, creep tests are carried out on wood samples undergoing constant bending stress along the beam. The moisture content of the samples is 12% obtained through a drying process in a kiln. The level of loading of the samples is fixed at 20% of the yield load. Then, the nonlinear least squares method is applied to the Zener rheological model to identify the optimal values of these parameters. The dynamic elastic modulus "E" and the dynamic constant viscosity "n" have been computed from the non-linear least square method while the instantaneous modulus of elasticity "E0", has been calculated from the Hooke’s law for the two wood species.
Keywords: Wood; creep; dynamic elastic modulus; dynamic viscosity constant; constant bending stress.